Potentiometric Studies on Transition Metal Complexes of Substituted Hydrazones - V. Katariya, Maya (Asian Journal of Chemistry, 2016)
Ligation properties of some phenyl hydrazones are investigated, using potentiometric technique in 75% dioxane-25% water (v/v) medium at 30ºC and 0.1 M ionic strength using Calvin-Bjerrum technique. The dissociation constants of various substituted phenyl hydrazones and the stability constants of complexes of these with some transition metal ions are reported. The effect of substitutents on the stability constants has been discussed.